Tolerance and Efficacy of a Dermocosmetic Containing Neurosensine® in Subjects with Eyelid Eczema - Tan J; Demessant A; Le Dantec G; Le Floc'h C; Kerob D (Dove Medical Press, 2023)
Jerry Tan,1 Ann'Laure Demessant,2 Guénaelle Le Dantec,2 Caroline Le Floc'h,2 Delphine Kerob2 1Department of Medicine and Windsor Clinical Research Inc, Western University, Windsor, ON, Canada; 2International Scientific Affairs, La Roche-Posay Laboratoire Dermatologique, Levallois-Perret, FranceCorrespondence: Jerry Tan, Western University, Department of Medicine and Windsor Clinical Research Inc, 300-2224 Walker Road, Windsor, ON, N8W 5L7, Canada, Tel +8615199719542, Email jerrytan1230@outlook.comBackground: Eyelid eczema (EE) is frequently observed in patients with an allergic or atopic diathesis. As for atopic eczema, restoring the skin barrier of the periocular region together with relieving clinical signs and symptoms is important in the management of EE. This study assessed the benefit and tolerance of a dedicated dermocosmetic (DC) in subjects with EE.Materials and Methods: Open-label study in adults with EE and sensitive skin. The DC was applied twice daily for 28 days. Dermatological signs (eczema, desquamation/dryness, erythema, swelling, roughness) and symptoms (itching, prickling, heat/burning sensation, tightness) on the periorbital region, as well as ophthalmological evaluation were assessed at Day 0, 14 and 28. Subjects assessed quality of life (QOL) using DLQI, the perceived benefit and cosmetic acceptability of the DC.Results: Overall, 41 subjects were included; 59% were women. The mean age was 52.4± 15.8 years; all subjects had periorbital sensitive skin. The DC immediately reduced the intensity of itching, prickling, heat/burning sensation and tightness. Clinical signs and symptoms had all significantly (p< 0.001) improved by Day 14 and were sustained to Day 28. The DC significantly (p< 0.001) improved the perception of irritation (73%) and swelling (66%) while soothing (59%) the periorbital skin regions at Day 28. QOL had improved at Day 28 (0.82± 1.0) compared to Day 0 (4.17± 2.23). No local adverse reactions were reported. Ophthalmological examinations paralleled the excellent dermatological tolerance of DC.Discussion: The tested DC is highly efficacious in reducing clinical signs and symptoms of eyelid eczema and was well tolerated.ClinicalTrials.gov Identifier: NCT05540496.Keywords: eyelid eczema, dermocosmetic, sensitive skin, periorbital skin